The Visually Impaired and how they Cope with Loneliness - Rokach, Ami; Rose, Alison; Berman, David (Journal of Psychology and Psychotherapy Research, 2021)
Loneliness has been termed a social epidemic, especially when experienced by people with sight challenges. The present study compared how the sight challenged and the blind cope with loneliness, compared to the general population groups, amongst a total of 187 participants. The questionnaire which we used, included 34-items to which a yes/no response was requested, and assessed the various ways that people cope effectively with loneliness. The questionnaire included six subscales of coping strategies, namely, Reflection and acceptance, Self-development and understanding, Social support network, Distancing and denial, Religion faith, and increased activity. As expected, the two populations differed significantly in their subscale scores, with the visually challenged scoring higher than the general population, on Self-development and understanding and the Religion and faith subscales. Interpretation of these results and their implications are discussed in further detail.